ANALISIS DAN PERANCANGAN PROSEDUR OPERASIONAL STANDAR ATAS SIKLUS PENGELUARAN KAS DALAM RANGKA MENINGKATKAN PENGENDALIAN INTERNAL - Marcelino, Natanael; Wehartaty, Tineke (Jurnal Akuntansi Kontemporer, 2018)
The study was conducted at Bumi Surabaya City Resort (Bumi Surabaya) which is a 5-star hotel in Surabaya. Bumi Surabaya already has Standard Operating Procedures (SOP) but the SOP is not relevant to the current condition. This study aims to update the SOP cash disbursement cycle of Bumi Surabaya, POS update needs to be done because SOP is a work guide for employees. In addition to updating SOP cash disbursement cycle, this study also evaluates the control activities for improved SOP cash disbursement cycle to be improved. The type of research used in making this research is case study. The focus of the research is the internal and external cash disbursement cycle, where there are 3 methods of internal cash disbursement and 4 external cash disbursement methods. The updated SOP is a simple POS and pilot project for Bumi Surabaya, Bumi Surabaya is expected to periodically evaluate POS so that the POS owned is relevant to the organization's latest condition.